The Arabidopsis thaliana phosphate starvation responsive gene AtPPsPase1 encodes a novel type of inorganic pyrophosphatase - May, Anett; Berger, Sigrid; Hertel, Thomas; Köck, Margret (Biochimica et biophysica acta, 2011)
Low inorganic phosphate (Pi) availability triggers metabolic responses to maintain the intracellular phosphate homeostasis in plants. One crucial adaptive mechanism is the immediate cleavage of Pi from phosphorylated substrates; however, phosphohydrolases that function in the cytosol and putative substrates have not been characterized yet. One candidate gene is Arabidopsis thaliana At1g73010 encoding an uncharacterized enzyme with homology to the haloacid dehalogenase (HAD) superfamily. This work reports the molecular cloning of At1g73010, its expression in Escherichia coli, and the enzymatic characterisation of the recombinant protein (33.5 kD). The Mg²(+)-dependent enzyme named AtPPsPase1 catalyzes the specific cleavage of pyrophosphate (K(m) 38.8 μM) with an alkaline catalytic pH optimum. Gel filtration revealed a tetrameric structure of the soluble cytoplasmic protein. Modelling of the active site and assay of the recombinant protein variant D19A demonstrated that the enzyme shares the catalytic mechanism of the HAD superfamily including a phosphorylated enzyme intermediate. The tight control of AtPPsPase1 gene expression underlines its important role in the Pi starvation response and suggests that cleavage of pyrophosphate is an immediate metabolic adaptation reaction. The novel enzyme, the first pyrophosphatase in the HAD superfamily, differs from classical pyrophosphatases with respect to structure and catalytic mechanism. The enzyme function could be used to discover unknown aspects of pyrophosphate metabolism in general.